PENGARUH PENGGUNAAN MEDIA CANVA TERHADAP MOTIVASI BELAJAR BAHASA INDONESIA SISWA SMK MUHAMMADIYAH 3 MAKASSAR - Apriadi; Muhammad Nawir; Kaharuddin (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2024)
The Effect of the Use of Canva Media on the Motivation to Learn Indonesian Language of Students of SMK Muhammadiyah 3 Makassar. Faculty of Teacher Training and Education, University of Muhammadiyah Makassar. Supervisor I Muhammad Nawir and Supervisor II Kaharuddin. The main problem in this study is whether there is an influence of the use of Canva media on the motivation of students to learn Indonesian Language of SMK Muhammadiyah 3 Makassar. This type of research is quantitative with an experimental method with a One-Shot Case Study research design, The sample in this study is students of class XI OTKP SMK Muhammadiyah 3 Makassar with a total of 23 students. This research procedure is carried out by observation, questionnaire and documentation methods. Based on the results of the study, the percentage of student activity in the first meeting learning was 78.69% and the percentage of student activity in the second meeting learning was 89.99% and from the results of the student response, an average score of 79.13% was obtained. The results of the infront statistical analysis showed that the result of the sig value was 0.063 where 0.063 > 0.05 which means that H0 was rejected or in other words H1 was accepted. So it can be concluded that there is an influence of the use of Canva media on the motivation of Indonesian Language learning students in grade XI OTKP at SMK Muhammadiyah 3 Makassar.